;Valorisation of banana peels by hydrothermal carbonisation: Potential use of the hydrochar and liquid by-product for water purification and energy conversion. (December 2020) - Yusuf, Ifrah; Flagiello, Fabio; Ward, Neil I.; Arellano-García, Harvey; Avignone-Rossa, Claudio; Felipe-Sotelo, Mónica
Abstract: Banana peels were used as feedstock to produce a carbon dense hydrochar for the removal of toxic metals from wastewater. Compared to the biomass feedstock (41.3% mass C), the banana peel hydrochar possesses higher carbon (54–72% mass C) and lower ash contents. The carbonised banana peels treated between 150 and 300 °C (1−2 h ) demonstrated an excellent ability to remove Cd 2+ (5–100 mg L −1 ), achieving 99% removal, in comparison with 75% for the raw peel. The liquid by-product generated in the carbonisation process was tested as feedstock in microbial electrochemical devices, showing significant reduction in the chemical oxygen demand levels (initially 10–25 10 3 mg L −1 ), associated with the production of electrical outputs; 81–85% reduction with microbial communities from compost, and 53–85% with anaerobic sludge. The results demonstrate the complete utilization of waste from mass cultivation of banana, providing a full-cycle solution for the pollution associated to this important crop. Graphical abstract: Unlabelled Image Highlights: Hydrothermal carbonisation is a sustainable solution for waste in banana industry. Hydrochars from banana peels are effective sorbents of Cd 2+ ion from water. Promising use of liquid by-product from hydrocharring for bioelectrochemical cells.